Integrating service quality, customer satisfaction, and brand gestalt in the context of multi-level marketing (MLM) companies - Theresia C. Lebo; Deske W. Mandagi (Institute of Computer Science (IOCS), 2023)
Ensuring service quality and customer satisfaction is essential for any company striving to establish a strong brand, attract new customers, and gain a competitive edge. Despite the increasing scholarly interest in service quality, customer satisfaction, and branding, there remains a dearth of empirical research on the nexus of these variables in relation to brand gestalt. The present study aims to address this theoretical gap by examining the link between service quality, customer satisfaction, and brand gestalt in the context of Multilevel Marketing (MLM) companies. This study employs a quantitative descriptive design, utilizing primary data obtained from a survey of 176 respondents who are either consumers or members of MLM companies. Data analysis is performed using Structural Equation Modeling (SEM) with the aid of the SmartPLS statistical program. The findings indicate that while service quality factors such as reliability, responsiveness, and empathy have no significant influence on customer satisfaction, tangibility and assurance aspects of service quality have a significant impact on customer satisfaction, which, in turn, has a significant influence on various dimensions of brand gestalt, including story, sensescape, servicescape, and stakeholder